2008
DOI: 10.1097/01.hcr.0000320076.19588.5c
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Improvement in Exercise Capacity and Symptoms Following Exercise Training in Interstitial Lung Disease

Abstract: Background: Interstitial lung disease (ILD) is characterised by exertional dyspnoea, exercise limitation and reduced quality of life. The role of exercise training in this diverse patient group is unclear. The aims of this study were to establish the safety of exercise training in ILD; its effects on exercise capacity, dyspnoea and quality of life; and whether patients with idiopathic pulmonary fibrosis (IPF) had similar responses to those with other types of ILD. Methods: 57 subjects with ILD (34 IPF) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
142
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 1 publication
9
142
3
1
Order By: Relevance
“…Nevertheless, in those studies the intervention was longer and more frequent. Despite having smaller changes than what was observed in other studies [44][45][46][47], the change of 41 and 45 m in the 6MWT was greater than we initially expected. Perera et al [38] estimated 20 m being the small meaningful change for 6MWT performed by seniors.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, in those studies the intervention was longer and more frequent. Despite having smaller changes than what was observed in other studies [44][45][46][47], the change of 41 and 45 m in the 6MWT was greater than we initially expected. Perera et al [38] estimated 20 m being the small meaningful change for 6MWT performed by seniors.…”
Section: Discussioncontrasting
confidence: 77%
“…In other studies [44][45][46][47], however, changes in walking distance are similar, or a little superior, to the 41 and 45 m obtained here. Nevertheless, in those studies the intervention was longer and more frequent.…”
Section: Discussionsupporting
confidence: 61%
“…This was not pulmonary rehabilitation and discussion ensued as to whether it should be included, given the paucity of literature otherwise. This study demonstrated modest improvements in functional exercise tolerance, dyspnoea and quality of life compared with telephone support 186. Importantly it was safe and feasible.…”
Section: Evidencementioning
confidence: 76%
“…Based on effects seen in our previous study,24 22 participants with dust-related ILD and 22 with CTD-ILD were required to detect a mean (SD) difference in 6MWD with 80% power between groups of 52 (40) m and 38 (30) m respectively 24 25. For participants with IPF, to detect differences of 29 or 34 m (SD 43 m) with 80% power, representing the upper and lower limits of the MID in IPF25 required 72 and 54 participants respectively.…”
Section: Methodsmentioning
confidence: 98%
“…Analysis of the other ILD subgroup was not performed as it represented a heterogeneous group of disease entities and not a distinct ILD subtype. Two per-protocol analyses were defined a priori including (1) those who completed the programme (attendance at 12 out of 16 sessions)24 and (2) those whose exercise training prescription was progressed according to the protocol. Categorical data were analysed using the Pearson χ 2 test.…”
Section: Methodsmentioning
confidence: 99%